Effectiveness of SELangkah SEHAT mental health mobile apps - Rusli, Mohammad Farhan; Zainal Abidin, Muhammad 'Adil; Mahmud, Siti Mariah; Badrol Hisham, Afaf Qamelia; Abdul Khaiyom, Jamilah Hanum; Kadir, Hayati (2023)
Background: Mental health application has grown in the recent year following the pandemic.The mobile apps offer opportunities to users for self-screening and self-management in a costeffective ways. However, the effectiveness of the apps is important to measure the usersresponse and to give feedback to health professional and developer to improve the delivery ofcontents. Purposes: This study aim to evaluate the effectiveness of a SELangkah SEHAT, a mentalhealth application develop for state-wide in Malaysia. Method: SELANGKAH SEHAT is an mental health application consist of screening tool,psychoeducation videos, mental health modules, helpline and psychiatrist subsidies program.The response rate and users characteristics for the app and each of the sub modules arepresented. The apps was started in September 2021 and data was collected until Jun 2023. Theapps available in English and local Malay language. Results: Since launching, the apps has go-live for 22 months. The number of registered userswere 20539 with number of users were 92478. There were 4 screening tools, with 15356 userscompleted the Perceived stress scale (PSS-10), 4709 users completed the Depression, Anxietyand Stress (DASS), 4401 users completed the Patient Health Questionnaire (PHQ-9), 5189completed the Geriatric Depression Scale (GDS-15). More than 4087 users completed theMental Health Literacy Score (MHLS). There were more than 63616 views on thepsychoeducation videos and 1285 users completed the mental health module. There were 2intervention offered in the apps, the hotlines which received 716 calls and 157 users benefitfrom psychiatric subsidy intervention program. Discussion: The SELangkah SEHAT mental health mobile apps received high response fromthe state-wide target group. The response for the self-screening questionnaire were high.However the response for the intervention hotlines was low. Users feedback should beconducted to evaluate their rating on the accessibility, usability and cultural compatibility asMalaysia is a multiracial country.